Some aspects of Turkic cooperation in Turkish sources and historiography (late nineteenth century - first quarter of the twentieth century) - Egemberdiyev, Мырзахан; Azmukhanova, Айман (Turkic Studies Journal, 2023)
The end of the 19th - the first quarter of the 20th centuries was a difficult time for Turkic peoples: the policy of spiritual colonization of tsarist Russia was in full swing, Jadid and Turkist movements were gaining strength, Turkic peoples increased their solidarity within the framework of these ideas, as a result of two revolutions the whole structure of Russian imperialist policy changed, the Bolshevik policy of atheism, famine and repression was implemented. This period has been comprehensively studied in domestic historiography and its «white spots» continue to be revealed today. However, this historical period has not yet been studied in the sources and historiography of Turkey, which is a brother country. The main sources of the chronological period we have chosen have been preserved in the archives of the Prime Minister of the Republic of Turkey, the Ottoman state libraries and the rare holdings of the National Library in Ankara. The studies and historiographical bases connected with the problems of Turkic peoples’ cooperation were examined from two perspectives: first, the scientific works of emigrated intellectuals of Turkic peoples - Zaki Validi Togan, Yusuf Akchora, Ali Mardana Topchubashi and others; second, after the collapse of the USSR, the works of scholars widely spread like Nadir Devlet, Ibrahim Marash, Rydvan Akin, Fusun Ustol, Nedjimtdin Seferzhioglu, Hakan Krimli and others, who have worked in Russia, Kazakhstan, Kyrgyzstan, Uzbekistan, Azerbaijan, Tatarstan, Bashkortostan and other archives and who have continued their research in Turkey. The main purpose of the article is complex analysis of Turkic peoples’ cooperation from the end of 19th - first quarter of 20th centuries in Turkish sources and historiography. In order to achieve this goal, Turkish sources and materials stored in the archives have been classified by means of comparative analysis, and on this basis the problems of Jadid movement, Turkism and Islam, Muslim issues, national identity and political-cultural struggle have been analysed based on the principle of historicism.